Under-ascertainment from healthcare settings of child abuse events among children of soldiers by the U.S. Army Family Advocacy Program. (January 2017) - Wood, Joanne N.; Griffis, Heather M.; Taylor, Christine M.; Strane, Douglas; Harb, Gerlinde C.; Mi, Lanyu; Song, Lihai; Lynch, Kevin G.; Rubin, David M.
Abstract: In cases of maltreatment involving children of U.S. Army service members, the U.S. Army Family Advocacy Program (FAP) is responsible for providing services to families and ensuring child safety. The percentage of cases of maltreatment that are known to FAP, however, is uncertain. Thus, the objective of this retrospective study was to estimate the percentage of U.S. Army dependent children with child maltreatment as diagnosed by a military or civilian medical provider who had a substantiated report with FAP from 2004 to 2007. Medical claims data were used to identify 0–17 year old child dependents of soldiers who received a medical diagnosis of child maltreatment. Linkage rates of maltreatment medical diagnoses with corresponding substantiated FAP reports were calculated. Bivariate and multivariable analyses examined the association of child, maltreatment episode, and soldier characteristics with linkage to substantiated FAP reports. Across 5945 medically diagnosed maltreatment episodes, 20.3% had a substantiated FAP report. Adjusting for covariates, the predicted probability of linkage to a substantiated FAP report was higher for physical abuse than for sexual abuse, 25.8%, 95% CI (23.4, 28.3) versus 14.5%, 95% CI (11.2, 17.9). Episodes in which early care was provided at civilian treatment facilities were less likely to have a FAP report than those treated at military facilities, 9.8%, 95% CI (7.3, 12.2) versus 23.6%, 95% CI (20.8, 26.4). The observed low rates of linkage of medically diagnosed child maltreatment to substantiated FAP reports may signal the need for further regulation of FAP reporting requirements, particularly for children treated at civilian facilities.